2021
DOI: 10.3390/su13168842
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Analysis of Train-Vehicle Accidents at Highway-Rail Grade Crossings in Florida

Abstract: Highway-rail grade crossing (HRGC) accidents pose a serious risk of safety to highway users, including pedestrians trying to cross HRGCs. A significant increase in the number of HRGC accidents globally calls for greater research efforts, which are not limited to the analysis of accidents at HRGCs but also understanding user perception, driver behavior, potential conflicting areas at crossings, effectiveness of countermeasures and user perception towards them. HRGC safety is one of the priority areas in the Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…Pada umumnya, jalur transportasi darat seperti rel kereta api banyak ditemukan berpotongan/bersinggungan langsung dengan jalan raya yang dapat menimbulkan kemacetan ataupun kecelakaan lalu lintas. Kecelakaan di perlintasan sebidang antara jalan raya dan rel kereta api menimbulkan risiko keselamatan yang serius bagi para pengguna jalan raya, termasuk pejalan kaki yang mencoba menyeberang di perlintasan sebidang (Singh et al, 2021).…”
Section: Pendahuluanunclassified
“…Pada umumnya, jalur transportasi darat seperti rel kereta api banyak ditemukan berpotongan/bersinggungan langsung dengan jalan raya yang dapat menimbulkan kemacetan ataupun kecelakaan lalu lintas. Kecelakaan di perlintasan sebidang antara jalan raya dan rel kereta api menimbulkan risiko keselamatan yang serius bagi para pengguna jalan raya, termasuk pejalan kaki yang mencoba menyeberang di perlintasan sebidang (Singh et al, 2021).…”
Section: Pendahuluanunclassified
“…''Table 8 shows that the highest number of fatal and serious injury crashes happens in winter conditions and the lowest number in the fall. Weather conditions such as low visibility, the presence of snow, and poor road conditions are contributing factors to highseverity crashes in the winter (55).…”
Section: Causes Of Severe Casualties Associated With Hrgc Crashesmentioning
confidence: 99%
“…They found that the four geometric features significantly affected at least one crash severity level and crossings with three main tracks contributed the most to long-term crash probabilities. Singh et al (2021) reviewed 578 crossings in Florida that experienced at least one collision from 2010 to 2019 and investigated various factors to understand the major causes behind crashes. They found that the majority of crashes occurred at public crossings that have either two-quad or four-quad gates, many of which were not illuminated, or urban crossings with high traffic volumes of high-speed traveling trains and vehicles.…”
Section: Background Informationmentioning
confidence: 99%